2022
DOI: 10.36778/jesya.v5i1.526
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kompetensi Sebagai Variabel Intervening Hubungan Pembelajaran Organisasi & Motivasi Spiritual Terhadap Kinerja Dosen dan Karyawan (Studi Pada IAIN Pekalongan)

Abstract: Penelitian ini bertujuan untuk menguji pengaruh Pembelajaran Organisasi dan Motivasi Spiritual Terhadap Kinerja Dosen dan Karyawan. Disamping itu, penelitian ini juga bertujuan untuk menguji peran Kompetensi sebagai variabel intervening. Untuk menguji variabel tersebut, peneliti memilih Dosen dan Karyawan di IAIN Pekalongan sebagai objek penelitian. Penelitian dilakukan dengan metode menyebarkan kuisioner kepada 100 Dosen dan Karyawan di IAIN Pekalongan. Pengambilan Sampel penelitian menggunakan t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The findings of this study are consistent with the findings of Zarkasi et al (2021), who found that competence might act as a positive and significant mediator between motivation and performance. In the same way, the results of this study are similar to those of Setiawan and Nafilah (2022), Arifin (2021), and Kahpi et al (2017). They all found that entrepreneurial motivation affects performance through competence.…”
Section: The Influence Of Entrepreneurial Characteristics On Entrepre...supporting
confidence: 92%
“…The findings of this study are consistent with the findings of Zarkasi et al (2021), who found that competence might act as a positive and significant mediator between motivation and performance. In the same way, the results of this study are similar to those of Setiawan and Nafilah (2022), Arifin (2021), and Kahpi et al (2017). They all found that entrepreneurial motivation affects performance through competence.…”
Section: The Influence Of Entrepreneurial Characteristics On Entrepre...supporting
confidence: 92%